دور التحول الرقمي في تحقيق الميزة التنافسية المستدامة للبنوك العمومية حالة البنك الوطني الجزائري - BNA -: The Role of Digital Transformation in Achieving Sustainable Competitive Advantage in Public Banking: The National Bank of Algeria BNA as a Model - نبيلة قرزيز,; محمد زيدان,; أحمد القطان, (Journal of North African Economies, 2025)
This study seeks to highlight the role of digital transformation in achieving sustainable competitive advantage in public banking by referring to the case of the National Bank of Algeria (BNA). Attaining such advantage became a prerequisite for the continuity of any bank, especially in light of technological innovation and the information revolution that the banking sector experienced lately; known as the process of digital transformation. The study relied on the deductive method when it comes to the theoretical part, and the inductive method in the practical part. The results showed that Algeria is continuously working on developing communications and internet infrastructure in order to allow banks to operate online at higher levels. It also notes that the National Bank of Algeria has provided several digital services as per the needs and requirements of its clients. Generally speaking, the bank is keen on keeping up with the technological innovations of the banking sector, and making good use of opportunities—local or international—in order to attain a sustainable competitive advantage. It remains, however, unable to provide world-class levels of digital services. We also provide some suggestions and recommendations that could allow Algerian public banks access to a smoother digital transformation, and support the adoption of novel mechanisms compatible with the banking environment of our age.